2011
DOI: 10.5897/ajb11.2539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed priming on growth and biochemical traits of wheat under saline conditions

Abstract: Effects of seed priming with 30 mM NaCl was determined on various growth and biochemical characters of 6 wheat varieties (Tatara-96, Ghaznavi-98, Fakhri Sarhad, Bakhtawar-92, Pirsabaq-2004 and Auqab-2000) under 4 salinity levels (0, 40, 80 and 120 mM). Statistical analysis of the data revealed that varieties, salinity and seed priming had significantly (P ≤ 0.05) affected germination (%), days to emergence, tillers plant-1 , leaves plant-1 and shoot chlorophyll-b contents (mg g-1 fresh weight). However, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…The compression force of the embryo and hydrolytic activities on the endosperm cell walls may deform the tissues that have lost their flexibility upon dehydration, producing free space and facilitating root protrusion after rehydration. Priming seeds with glucose confirmed the same logic by reducing the hazards of salinity.Increase in germination % by priming techniques in canola (Hassanpoughdam et al, 2009;Heshmat et al, 2011;Aboutalebian et al, 2012;Mousavi et al, 2019;Khan et al, 2021;Zhu et al,2021), calendula (Sedghi et al, 2010, Wheat (Jamal et al, 2011;Michal et al, 2012;Worku et al 2016;Khan et al 2018;Abbas et al, 2018;Ehtaiwesh & Almajdor, 2021), alfalfa (Jorjandi & Sirchi, 2012), calotropis (Taghvaei et al, 2012, soyabean (Ahmadvand et al, 2012), Aeleorupus (Nejad et al, 2013), cumin (Shoor et al, 2014, maize (Akter et al, 2018;Shah et al,2021), Vicia (Aydinoghlu et al, 2019, barley (Tabatabaei & Ansari, 2020), camelina (Huang et al, 2021) confirmed our results regarding enhancement of percent emergence of wheat by presowing seeds treatments. On the contrary, studies on wheat (Afzal et al, 2005;Akbarmoghaddam et al, 2011;Biabani et al, 2013), canola (Bybordi & Tabatabaei, 2009;Mohammadi et al, 2010), and maize (Akter et al., 2018) declared priming techniques as non-efficient in inducing positive effects on germination of plants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The compression force of the embryo and hydrolytic activities on the endosperm cell walls may deform the tissues that have lost their flexibility upon dehydration, producing free space and facilitating root protrusion after rehydration. Priming seeds with glucose confirmed the same logic by reducing the hazards of salinity.Increase in germination % by priming techniques in canola (Hassanpoughdam et al, 2009;Heshmat et al, 2011;Aboutalebian et al, 2012;Mousavi et al, 2019;Khan et al, 2021;Zhu et al,2021), calendula (Sedghi et al, 2010, Wheat (Jamal et al, 2011;Michal et al, 2012;Worku et al 2016;Khan et al 2018;Abbas et al, 2018;Ehtaiwesh & Almajdor, 2021), alfalfa (Jorjandi & Sirchi, 2012), calotropis (Taghvaei et al, 2012, soyabean (Ahmadvand et al, 2012), Aeleorupus (Nejad et al, 2013), cumin (Shoor et al, 2014, maize (Akter et al, 2018;Shah et al,2021), Vicia (Aydinoghlu et al, 2019, barley (Tabatabaei & Ansari, 2020), camelina (Huang et al, 2021) confirmed our results regarding enhancement of percent emergence of wheat by presowing seeds treatments. On the contrary, studies on wheat (Afzal et al, 2005;Akbarmoghaddam et al, 2011;Biabani et al, 2013), canola (Bybordi & Tabatabaei, 2009;Mohammadi et al, 2010), and maize (Akter et al., 2018) declared priming techniques as non-efficient in inducing positive effects on germination of plants.…”
Section: Resultsmentioning
confidence: 99%
“…The previous workers have confirmed stimulatory tendencies of pre-soaking amendments on various traits of plants like Triticum (Iqbal & Ashraf, 2007), Helianthus (Kaya et al, 2006), chickpea (Kaur et al, 2002), Capsicum (Patade et al, 2011), Glysine max (Sadeghi et al, 2011), maize (Foti et al, 2008), cucumber (Ghasemi-Golezani & Esmaeilpour, 2008). The priming tendencies of various chemicals such as Calcium Chloride (Fuller et al, 2012;Taghvaei et al, 2012;Abbas et al, 2018), Sodium Chloride (Jamal et al, 2011;Nejad et al, 2013;Shoor et al, 2014), Zinc Oxide nano-particles (Al-salama 2022), sorghum water (Huang et al, 2021), Potassium Nitrate (Ahmadvand et al, 2012), aspirin (Ehtaiwesh & Almajdob, 2021), Potassium Permangante (Hassanpouraghdam et al, 2009;Hassanpouraghdam et al, 2009), vitamin B12 (Jorjandi & Sirchi, 2012), plant hormones (Sedghi et al, 2010;Salih et al, 2022), PEG-6000 (Aydinoglu et al, 2019;Fuller et al, 2012), Ascorbic Acid, Potassium Silicate, Proline and Spermidine (Feghhenabi et al, 2020) had been already studied. In this study, we have explored the priming tendencies of glucose on a prominant oilyielding plant, the canola for the first time keeping in view the importance of glucose for initial stages of germination of plants.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…It was found that humic acids reduced the sodium input of plants in soils where their levels were evaluated. e absorption of other elements by plants remained practically unchanged (Jamal et al, 2011;Jarošová et al, 2016). e physiological effects of humic substances are also manifested in the optimization of osmotic processes and the regulation of the photosynthetic pigment content in young plants.…”
Section: Introductionmentioning
confidence: 99%
“…Humic acids are capable of demonstrating their antistress effect on plants at unfavorable soil and weather conditions of their cultivation (Jamal Y et al, 2011;Jarošová M et al, 2016).…”
Section: Introductionmentioning
confidence: 99%